In order to solve this problem, you need to use point slope form of a line. The formula for that is...
y - y₁ = m(x - x₁)
Let x₁ be 0
Let y₁ be 3
Remember that slope intercept form of a line is y = mx + b, where m stands for the slope and b stands for the y intercept.
y - 3 = -5(x - 0)
y - 3 = -5x + 0
+ 3 + 3
--------------------------
y = -5x + 3
The final answer in slope intercept form is y = -5x + 3. I hope this makes sense to you. If you have any more questions about math, let me know and I can try to help you figure them out :-)